STRATEGIC MANAGEMENT IN THE ERA OF GLOBALIZATION CHANGES: MINIMIZATION OF ENTROPY AS A GUARANTEE OF FIGHTING ECONOMIC CRIME - VOSTRIAKOV, Oleksandr; TEPLIUK, Mariiа (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores strategic management in the era of the new normal, characterized by significant economic and social changes driven by globalization, digitalization, and innovative development. It focuses on minimizing entropy as a crucial factor in effectively combating economic crime. In this context, entropy is viewed as a measure of chaos and disorganization within organizational processes, creating favorable conditions for various forms of economic crime, including fraud, corruption, and financial malfeasance. The authors emphasize the importance of adaptive strategies and innovative approaches to reduce entropy, enhancing predictability, transparency, and management efficiency. The study analyzes the key challenges faced by enterprises in a dynamic economic environment, particularly in the context of digital transformation and technological advancements. The implementation of modern technologies such as big data, artificial intelligence, and blockchain is presented as an effective tool for reducing entropy and enhancing organizational resilience. Furthermore, the article provides recommendations for integrating entropy management into strategic planning processes to ensure sustainable enterprise development and increased competitiveness. The impact of digital transformation on business processes and management approaches is also examined, demonstrating how enterprises can not only adapt to new conditions but also effectively counter economic crime. The role of corporate culture in establishing ethical standards and legal compliance is highlighted as a critical factor in reducing the risks of criminal activity. The findings of the study confirm that minimizing entropy in strategic management is essential for creating a secure and stable business environment in the new normal..
Keywords: strategic management; entropy; economic crime; new normal; digital transformation; organizational resilience; adaptive strategies; sustainable development; innovation; globalization changes